Advances in understanding of presbycusis. Issue 9 (4th April 2019) - Tawfik, Kareem O.; Klepper, Kristin; Saliba, Joe; Friedman, Rick A.
Abstract: The pathophysiology of age‐related hearing loss (ARHL), or presbycusis, involves a complex interplay between environmental and genetic factors. The fundamental biomolecular mechanisms of ARHL have been well described, including the roles of membrane transport, reactive oxygen species, cochlear synaptopathy, vascular insults, hormones, and microRNA, to name a few. The genetic basis underlying these mechanisms remains under‐investigated and poorly understood. The emergence of genome‐wide association studies has allowed for the identification of specific groups of genes involved in ARHL. This review highlights recent advances in understanding of the pathogenesis of ARHL, the genetic basis underlying these processes and suggests future directions for research and potential therapeutic avenues.